Tracing of Human Tumor Cell Lineages by Mitochondrial Mutations - Refinetti, Paulo; Morgenthaler, Stephan; Thilly, William G.; Arstad, Christian; Ekstrøm, Per O. (Frontiers in Oncology, 2020)
Background: Previous study have shown the value in studying lineage tracing in human tumors. However, a tumor is not a two-dimensional struc- ture, rather a three-dimensional (3D) one. To better understand how a tu- mor, and its corresponding metastasis grow a 3D view is therefore necessary. Results: Using somatic mitochondrial mutations as marker for lineage trac- ing, it is possible to identify and follow tumor specific cell lineages. Using cycling temperature capillary electrophoresis (CTCE) a total of 8 tissues from 5 patients (4 primary tumors and 4 metastasis) containing clear mito- chondrial markers of tumor lineages were selected. From these 8 tissues over 9500 Laser capture microdisection (LCM) samples were taken and analysed, in a way that allows 3-rendering of the observations. Results enable the 3D visualisation of the patterns formed by cell lineages in primary tumors and their corresponding metastasis. Conclusion: Using CTCE combined with LCM, it is possible to study the 3D patterns formed by tumors and metasta- sis as they grow. These results clearly show that the majority of the volume occupied by a tumor is not composed of tumor derived cells. These cells are most likely recruited from the neighbouring tissue.